The Effect of Halal Brand Personality, Brand Experience, User Experience and E-Service Quality on Brand Loyalty (Case Study on Muslim Consumers of Skintific Products in Surabaya) - Salsabila, Sania (Universitas Darussalam Gontor, 2024)
**English**This study aims to determine the effect of halal brand personality, brand experience, user experience, and e-service quality on brand loyalty simultaneously and partially. This research uses descriptive quantitative methods. The population in this study were 100 Muslim consumers of Skintific products in Surabaya. The sample in the study was determined by the lemeshow formula and obtained 100 respondents. The sampling technique used purposive sampling. The data collection technique used a questionnaire with 36 statement items and was measured using a Likert scale of 1 to 5 which had been tested for validity and reliability. The data analysis technique used is multiple linear regression analysis to answer the hypothesis. The results showed that from the partial test, the halal brand personality variable had a significant effect on brand loyalty with a tcount of 2.138> table 1.661 and a significant value of 0.035 <0.05. From the variable. From the brand experience variable, it has a significant effect on brand loyalty with tcount 2.055> table 1.661 and a significant value of 0.043 <0.05. From the user experience variable, it has a significant effect on brand loyalty with a tcount of 3.782> table 1.661 and a significant value of 0.000 <0.05. From the e-service quality variable, it has a significant effect on brand loyalty with tcount 2,764> table 1,661 and a significant value of 0.007 <0.05. Then, the simultaneous test of halal brand personality, brand experience, user experience and e-service quality variables has a significant effect on brand loyalty showing F count 20,261> F table 2,467 with a significant value of 0.000 <0.05. The R Square result of 43.8% shows the influence of halal brand personality, brand experience, user experience, and e-service quality on brand loyalty. While 56.2% is influenced by other variables outside the study **Indonesia**Penelitian ini bertujuan untuk mengetahui pengaruh halal brand personality, brand experience, user experience, dan e-service quality terhadap brand loyalty secara simultan maupun parsial.Penelitian ini menggunakan metode kuantitatif deskriptif. Populasi pada penelitian ini sebanyak 100 konsumen muslim produk Skintific di Surabaya. Sampel pada penelitian ditentukan oleh rumus lemeshow dan diperoleh 100 reponden. Teknik pengambilan sampel menggunakan purposive sampling. Teknik pengumpulan data menggunakan kuesioner dengan 36 butir pernyataan dan diukur menggunakan skala likert 1 sampai 5 yang telah diuji validitas dan realibilitasnya. Teknik analisis data yang digunakan yaitu analisis regresi linear berganda untuk menjawab hipotesis. Hasil penelitian menunjukkan dari uji parsial variabel halal brand personality berpengaruh signifikan terhadap brand loyalty dengan thitung 2,138 > tabel 1,661 dan nilai signifikan 0,035 < 0,05. Dari variabel. Dari variabel brand experience berpengaruh signifikan terhadap brand loyalty dengan thitung 2,055 > tabel 1,661 dan nilai signifikan 0,043 < 0,05. Dari variabel user experience berpengaruh signifikan terhadap brand loyalty dengan thitung 3,782 > tabel 1,661 dan nilai signifikan 0,000 < 0,05. Dari variabel e-service quality berpengaruh secara signifikan terhhadap brand loyalty dengan thitung 2,764 > tabel 1,661 dan nilai signifikan 0,007 < 0,05. Kemudian, Uji simultan variabel halal brand personality, brand experience, user experience dan e-service quality berpengaruh signifikan terhadap brand loyalty menujukkan F hitung 20,261 > F tabel 2,467 dengan nilai signifikan 0,000 < 0,05. Hasil R Square sebesar sebesar 43,8% menunjukkan pengaruh halal brand personality, brand experience, user experience, dan e-service quality terhadap brand loyalty. Sedangkan 56,2% dipengaruhi variabel lainnya diluar penelitian.